Avoidance behaviors in a campus residential environment - Hibdon, Julie A. (Criminology, criminal justice, law & society, 2016)
Over the last several decades, campus crime, victimization, and incidents of violence have been a focal concern for campus administrators and have generated interest in the research community. Studies have provided insight into the nature of campus crime and victimization, as well as whether these concerns relate with fear of crime and perceptions of risk. Less consideration has been given to the relationship between these variables and the use of protective action among college students, especially those residing in student housing environments. This study uses survey data from students residing in campus housing at a Midwestern university to examine how fear of crime, perceived risk of victimization, and other relevant concepts predict student protective action and, more specifically, the use of avoidance behaviors. The findings suggest that White and female residents, as well as those who were more fearful of crime and had prior victimization experiences, were more likely to engage in avoidance behaviors.